Wear properties of a bulk nanocrystalline Fe-1at% Zr alloy. (June 2022) - Cong, Y.B.; Chen, Y.Z.; Shan, G.B.; Zhang, W.X.; Liu, F.; Li, Q.; Xu, X.J.
Abstract: In this work, a bulk nanocrystalline Fe-1 at% Zr alloy was prepared by combining mechanical alloying and spark plasma sintering techniques. Sliding wear experiments were conducted to investigate wear behaviors of the bulk nanocrystalline samples under different testing conditions. The results show that the bulk nanocrystalline Fe-1 at% Zr alloy exhibits a superior wear resistance. Taking Si3 N4 and Al2 O3 spheres with a diameter of 3 mm as the counterfaces, under a load of 1 N, a displacement amplitude of 1 mm, and a sliding frequency of 0.5 Hz, the specific wear rate of the bulk NC Fe-1 at% Zr alloy is determined to be in the order of 10 −7 mm 3 N −1 m −1 . When the counterface, the displacement amplitude, and the sliding frequency are a Al2 O3 sphere with a diameter of 3 mm, 1 mm and 0.5 Hz, respectively, the main wear mechanism of bulk NC Fe-1 at% Zr alloy corresponds to the abrasive wear under the loads of 1 and 5 N. Under the same testing conditions, taking the Si3 N4 sphere with a diameter of 3 mm as the counterface, the main wear mechanism of the alloy is attributed to the abrasive wear under the load of 1 N; while the load is increased to 5 N, the main wear mechanism of the alloy becomes the delamination of the interfacial layer. Graphical Abstract: ga1 Highlights: The wear resistance of the bulk NC Fe-1 at% Zr alloy prepared by SPS was tested. The wear mechanism of the bulk NC Fe-1 at% Zr alloy under different experimental conditions were discussed. The bulk NC Fe-1 at% Zr alloy exhibits higher wear resistance than NM400 wear-resistant steel.